Penatalaksanaan Fisioterapi Komprehensif Pada Kasus Pasca Coronary Artery By Pass Grafting Et Causa Coronary Artery Disease Involving 3 Vessels (CAD3VD): Case Report - Pramudiana, Nurisma; Pristianto, Arif (Universitas Muhammadiyah Surakarta, 2022)
Coronary heart disease is a malfunctioning of the heart caused by stenosis of the heart blood vessels which can affect one or more arteries. In these cases the patient had Triple Vessels Disease (3-VD), where there was ≥50-70% stenosis in most of the main branches of the heart blood vessels, then the patient underwent a revascularization operation Coronary Artery Bypass Grafting (CABG) with a postoperative condition, namely pain. in the sternum and lower right leg, accumulation of pulmonary sputum, decreased thoracic expansion, shortness of breath, decreased activity and functional ability. The management of physiotherapy that is given is chest physiotherapy and active and passive exercises in extremity. After 3 times of therapy, the results obtained from the degree of shortness of T0: 5 to T3: 3, the decrease in pain T0: 6 to T3: 3, then tenderness T0: 6 to T3: 3 and silent pain T0: 4 to T3: 3 increased the difference in thoracic expansion in the axilla T0: 1 cm becomes T3: 2 cm, at ICS T0: 1 cm changes to T3: 2 cm and there has been no increase in the xypoideus process, by 2 cm at T0 and T3. Activity and functional abilities were calculated using the Barthel index on T0 of the total dependency category, changing to T3: weight dependence. Chest physiotherapy and active-passive exercises in extremity can alleviate problems in post-CABG surgery.